Perencanaan Architecture Enterprise Sistem Informasi Pembelian, Penjualan Dan Keuangan Menggunakan Zachman Framework Untuk Meningkatkan Efektivitas Sistem Informasi Di PT. Aria Putra Rambutan - Apip Wahdan Ismail; Sofia Dewi (Jurnal Dimamu, 2023)
The role of the development of information technology today has had a significant impact, information technology has emerged as one of the solutions to overcome human problems. Based on the results of observations regarding the problems and facts at PT. Aria Putra Rambutan can see that the current system does not provide optimal results for the company's business activities. Therefore, companies are required to make an enterprise architecture plan that aims to be able to connect existing strategies or business processes with information technology so as to produce an optimal system. This study aims to make architectural plans that can process databases according to company needs, design information systems that can facilitate business processes and control business processes, create blueprints of technology architecture to make it easier to see the flow of business processes and technology. For analysis of enterprise information technology architecture or Enterprise Architecture is to use the ZACHMAN FRAMEWORK methodology, there are 4 stages to be carried out in this thesis, namely, Scope/Contextual, Business Process, System model, and Technology Model. This research produces principles in the manufacture of corporate architecture, then produces a blueprint for the design of the information system architecture.